Efeitos imediatos de três modificações da técnica de corrida na cinemática do membro inferior e tronco e no conforto em corredores sadios: um estudo experimental - Santos, Ana Flávia dos (2014)
In Brazil, it is estimated a 30-fold increase in the number of runners in the last 15 years. This growing number of practitioners has been noticed all over the world. It is known that most of the injuries that occur during this activity involves the knee joint (42,1%) and, the Patellofemoral Pain (PFP) is the commonest. Recently, it has been hypothesized that running technique modification (such as, landing with the forefoot on the ground [FFOOT], increasing 10% of the step rate [10% SR] and increasing the trunk flexion [TFLEX]) has the potential to reduce the demand on the knee joint. However, no study evaluated the effects of these running techniques on the lower limb and trunk three-dimensional joint kinematics and on comfort reported by runners. Thus, this study aimed to evaluate the immediate effects FFOOT, 10% SR and TFLEX on the trunk, hip, knee and ankle kinematics and on the subjective assessment of comfort during running. Thirty-one healthy rearfoot strike-landing runners (20 males, 11 females) were evaluated. For such, the Qualisys Motion Capture System was used to collect data during Usual Running (USRUN) and the other three running techniques and, a visual analogue scale was used to evaluate comfort in each condition. The variables of interest were collected during initial foot contact on the treadmill. For statistical analysis, it was used the multivariate analysis of variance (MANOVA) with repeated measures (alpha level of 0.05). During the FFOOT, it was shown reduction in the knee external rotation (P < 0.001), hip flexion (P < 0.001), adduction (P = 0.001), internal rotation (P < 0.001), greater knee adduction (P = 0.016), knee flexion (P < 0.001) and plantar flexion (P < 0.001). The 10% SR demonstrated diminished knee external rotation (P = 0.001), hip internal rotation (P = 0.008) and, hip flexion (P = 0.001), however, there was greater knee flexion (P = 0,042). The TFLEX increased knee adduction (P = 0.001), hip flexion (P < 0.001), trunk flexion (P < 0.001), but decreased plantar flexion (P = 0.003). The USRUN was the most comfortable technique (P = 0.033 0.002). Therefore, we were to conclude that the three running technique modifications can minimized the knee and hip movements in the frontal and transverse planes that are associated with greater stress on the patellofemoral joint. In addition, the FFOOT and 10% SR techniques resulted in increased knee flexion that could improve the impact forces absorption. It is believed that a gradual transition to these running techniques may improve comfort.